E-049 Thrombectomy forces and mechanical properties of emboli in large vessel occlusion stroke. (4th August 2020) - Liu, Y; Zheng, Y; Reddy, A; Gebrezgiabhier, D; Davis, E; Cockrum, J; Gemmete, J; Chaudhary, N; Griauzde, J; Pandey, A; Shih, A; Savastano, L
Abstract : Introduction: Mechanical thrombectomy using a suction catheter, a stent or the combination of both has recently become a standard of care for large vessel occlusion (LVO) stroke. However, complete recanalization (mTICI=3) with the best neurological outcome can be achieved in only 50% of the cases. In addition, multiple devices and passes are usually needed to recanalize, prolonging procedure times, increasing the risks of vessel damage. To improve our understanding of the interaction between the embolus and thrombectomy devices, in this study we first created a test bed of LVO and analyzed the forces during recanalization. We provided mechanistic explanations of the observations and failure modes by mechanically characterizing a range of emboli retrieved from patients with LVO stroke. Materials and Methods: An LVO test bed with anatomically accurate glass model of an MCA bifurcation was created with physiological flow and pressure. Thrombectomy procedures to remove embolus analogs (EAs) were performed 10 times each using the ADAPT and CAPTIVE techniques. The mechanical responses of the EAs to the action of the thrombectomy devices were recorded and analyzed and deemed to be mostly due to tensile load. To quantify the tensile properties of emboli, 37 emboli retrieved from 20 patients were collected and tested on a customized tensile test machine. The machine applied uniaxial tensile load to the emboli to mimic the vacuum suction and stent pull during thrombectomy procedure. The elongation, thinning, and dissociation were quantified to calculate the embolus strength, represented by ultimate strain (maximum elongation) and ultimate stress (maximum force per unit cross-sectional area). Results: The forces involved in the embolus removal process were categorized into: 1) retrieval forces including vacuum suction or stent pull, 2) resistance forces including static friction and adhesion at the embolus-vascular interface, the preload of the embolus protruding into branching arteries, and the pressure difference proximal and distal to the embolus, and 3) emboligenic forces including dynamic friction at the embolus-vascular interface and the blood pressure and shear at the embolus interface. In order to remove emboli, retrieval forces need to be larger than the resistance forces. If the retrieval force is larger than the strength of the embolus, the embolus will undergo multistage fracture, leading to embolization. The tensile testing of patients' emboli revealed similar behavior, including elongation under tension and multi-stage fracture patterns. The ultimate strain ranged from 1.05 to 4.89 (2.41 ± 1.04 [mean ± SD]) and the ultimate stress ranged from 63 to 2396 kPa (569 ± 695 kPa). The ultimate strain of the emboli increased with a higher platelet percentage, and the ultimate stress increased with a higher fibrin percentage and decreased with a higher red blood cell percentage. Conclusion: Suction catheters and the stents recanalize by applying tensile force to dislodge and remove the emboli. The tensile force leads to embolus elongation and thinning until dissociation, which may cause iatrogenic embolization. The ability to resist dissociation is determined by embolus strength, which significantly correlates with composition and varies within and among patients and within the same embolus. Disclosures: Y. Liu: None. Y. Zheng: None. A. Reddy: None. D. Gebrezgiabhier: None. E. Davis: None. J. Cockrum: None. J. Gemmete: None. N. Chaudhary: None. J. Griauzde: None. A. Pandey: None. A. Shih: None. L. Savastano: 4; C; Endovascular Engineering.